Isolation, Serotyping, and Molecular Detection of Bovine FMD Virus from Outbreak Cases in Abaʼala District of Afar Region, Ethiopia - Teshager Dubie; Tsedale Amare (Veterinary Medicine International)
Background. On the basis of FMDV outbreak cases, a cross-sectional study was undertaken to collect samples from January 2019 to March 2020 intended for isolation, serotyping, and molecular detection of FMDV in the study district. The purposive sampling method was applied to select the study area for the reason of the presence of FMD outbreak case report during the study period. Totally, 27 FMD clinical samples were collected from affected study population during field outbreak. Out of 27 samples, 18 of them were inoculated on cultured Baby hamster kidney (BHK-21) monolayer cells, and all 27 samples were tested using conventional RT-PCR and sets of specific universal primers. Finally, the PCR products were visualized with UV illumination and imaged with gel documentation system. Results. The current study results revealed that out of 18 clinical samples subjected to virus isolation, 72.2% (n = 13) of these cultures exhibited FMDV-induced cytopathic effect (CPE) and the identified serotype was SAT-2 FMD virus. Out of 27 clinical samples tested by conventional RT-PCR, only 12 FMDV samples were found to be FMDV positive by universal primers. Out of 27 samples detected by conventional RT-PCR, only 12 FMDV samples were found to be FMDV positive by universal primers. Conclusions. Our study finding indicated that FMDV is prevalent in the study area and FMDV serotype SAT-2 was the causality for the outbreaks of the disease in the study area. Hence, region-wise FMD outbreak investigation, further phylogenetic analysis, and vaccine matching field isolates should be carried out for effective vaccine development to control the disease.